THE DEVELOPMENT OF STUDENT WORKSHEETS BASED ON GUIDED DISCOVERY ON THE MUTATION SUB TOPIC - TRISNA NINGROM, DESIANA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Mutation sub Topic is one of an abstract learning material. Learning object in this sub topic cannot be observed using light microscope, thus it needs learning media that able to illustrated the material itself. So, this material would be simply understand by students. The objectives of this research is to produce and to described the theoritical feasibility of student worksheet. This research conducted based on Four-D (4-D) development methods. The result of this research indicates that developed student worksheets based on guided discovery on the mutation material as learning media could be declared feasible with worksheets validation and material validation score namely 86% and 90% Keywords: student worksheet, guided discovery, mutation.